Analisa Hubungan Tingkat Pengetahuan Salat terhadap Praktek Pelaksanaan Salat Pada Pasien Rawat Inap di Rumah Sakit Umum Daerah Haji Makassar - Zulfasari Ibrahim; Rachmat Faisal Syamsu; Muhammad Jabal Nur; Moch Erwin Rachman; Zulfitriani Murfat (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
In Islam, prayer (salat) is a fundamental obligation that must be performed under all circumstances, including during illness. Muslim patients have high spiritual needs, in which religious practices serve as a source of strength in coping with disease. Although Islam provides concessions (rukhsah) in performing prayer for the sick, limitations in patients’ understanding of how to perform prayer according to their health conditions are still found. This lack of knowledge may affect the proper practice of prayer during hospitalization. Therefore, this study aims to identify patient characteristics related to the practice of prayer, to examine the level of knowledge of the five daily prayers in relation to their practice among patients, and to analyze patients’ overall level of knowledge regarding prayer. This study employed a quantitative method with a cross-sectional design. The results show that patient characteristics, particularly productive age and higher educational level, contribute to their ability to perform prayer during hospitalization. A significant relationship was found between the level of knowledge of prayer and its practice, where better understanding was associated with more optimal religious practice. Overall, most patients had a high level of knowledge of prayer, although a small proportion still had low knowledge, indicating the need for spiritual education. It can be concluded that the level of knowledge of prayer is associated with the quality of prayer practice among Muslim patients at RSUD Haji Makassar. Strengthening spiritual education is needed to support the fulfillment of patients’ religious needs during hospitalization.